Words, Sense, and Denotation Meaning in Pupuh Ginanti “Saking Tuhu Manah Guru” - Widiadnya Putri, I Gusti Ayu Vina; Santika, I Dewa Ayu Devi Maharani; Winartha, Ida Bagus Gde Nova (SPHOTA: Jurnal Linguistik dan Sastra, 2024)
This study aims to analyze words, sense, and denotation in Pupuh Ginanti, entitled "Saking Tuhu Manah Guru". Pupuh is one of the Balinese poem that is still preserved nowadays. This pupuh has a moral value that needs to be conveyed to listeners. The message is conveyed through the form of the words that compose it. Every word or sentence in a literary work has meant that unknowingly, so an analysis of the word, sense, and meaning of denotation in Pupuh Ginanti needs to be discussed more deeply. Data was initially categorised for this study using some kind of word classification. Start data coding after categorization. By analysing text-based data, data analysis techniques employ qualitative methods.  The researcher also employed documentation strategies to obtain the data. The theory used in this study is (Allan, 2014) to analyze sense meaning and supported by theory from (Kreidler, 2002) to analyze denotation meaning. This study uses a descriptive qualitative approach. The result of this research is that the meaning of the poem in Pupuh Ginanti entitled "Saking tuhu manah guru" has a denotative meaning and sense meaning in each line. Sense meaning in this poem was used to clarify the message to be conveyed by the author.